2021
DOI: 10.37031/jt.v19i2.188
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Spasial Tingkat Bahaya Banjir Desa Amasing Kali Dengan Hec-RAS 2D

Abstract: The phenomenon of flooding that occurs in various parts of the world continues to increase, both in terms of frequency and amplitude. Without neglecting the morphology of the region, global climate change and changes in land use as a result of economic growth are the main factors causing this disaster. Understanding flood characteristics, be it discharge, inundation height, and their distribution in an area is very important as a basis for determining flood control efforts. This study aims to analyze the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In measuring dispersion to obtain statistical parameters, the Normal Distribution, Gumbel, Normal Log, and Log Pearson III were calculated (Ben Khalfallah and Saidi, 2018;Rauf, 2021). It was found that the Log Pearson III meets the requirements in the calculation of the statistical parameter dispersion and will be used for further analysis.…”
Section: Frequency Of Rainfallmentioning
confidence: 99%
See 2 more Smart Citations
“…In measuring dispersion to obtain statistical parameters, the Normal Distribution, Gumbel, Normal Log, and Log Pearson III were calculated (Ben Khalfallah and Saidi, 2018;Rauf, 2021). It was found that the Log Pearson III meets the requirements in the calculation of the statistical parameter dispersion and will be used for further analysis.…”
Section: Frequency Of Rainfallmentioning
confidence: 99%
“…Natural disasters are phenomena significantly impacting either the natural environment or human, with a high chance of damage (Popescu and Bărbulescu, 2023). Indonesia is a country with high potential for natural disasters, influenced by geological conditions and climatic factors (Rauf, 2021). Indonesia's National Disaster Management Agency noted throughout 2022 that natural disasters in Indonesia had occurred ± 2,111 times, be it extreme weather, landslides, drought, earthquakes, fires, tidal waves, abrasion, and floods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplikasi inidifokuskan pada analisis hidrolika aliran pada penampang saluran terbuka baik untu kaliran 1D dan 2D (Brunner, 2016). Hasil analisis aplikasi ini dapat memberikan gambaran pola sebaran banjir dan tinggi genangan yang terjadi pada sebuah wilayah dengan cukup baik (Sholichin & Prayogo, 2019), (Rauf, 2021).…”
Section: Pendahuluanunclassified